Transcriptomic Insights into Host Metabolism and Immunity Changes after Parasitization by Leptopilina myrica - Junwei Zhang; Jieyu Shan; Wenqi Shi; Ting Feng; Yifeng Sheng; Zixuan Xu; Zhi Dong; Jianhua Huang; Jiani Chen (Insects, 2024)
Parasitoids commonly manipulate their host’s metabolism and immunity to facilitate their offspring survival, but the mechanisms remain poorly understood. Here, we deconstructed the manipulation strategy of a newly discovered parasitoid wasp, L. myrica, which parasitizes D. melanogaster. Using RNA-seq, we analyzed transcriptomes of L. myrica-parasitized and non-parasitized Drosophila host larvae. A total of 22.29 Gb and 23.85 Gb of clean reads were obtained from the two samples, respectively, and differential expression analysis identified 445 DEGs. Of them, 304 genes were upregulated and 141 genes were downregulated in parasitized hosts compared with non-parasitized larvae. Based on the functional annotations in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, we found that the genes involved in host nutrition metabolism were significantly upregulated, particularly in carbohydrate, amino acid, and lipid metabolism. We also identified 30 other metabolism-related DEGs, including hexokinase, fatty acid synthase, and UDP-glycosyltransferase (Ugt) genes. We observed that five Bomanin genes (Boms) and six antimicrobial peptides (AMPs) were upregulated. Moreover, a qRT-PCR analysis of 12 randomly selected DEGs confirmed the reproducibility and accuracy of the RNA-seq data. Our results provide a comprehensive transcriptomic analysis of how L. myrica manipulates its host, laying a solid foundation for studies on the regulatory mechanisms employed by parasitoid wasps in their hosts.